Tacripyrines, the First Tacrine-Dihydropyridine Hybrids, as Multitarget-Directed Ligands for the Treatment of Alzheimer's Disease - Marco-Contelles, Jose (2015)
Tacripyrines (1-14) have been designed by combining an ACNE inhibitor (tacrine) with a calcium antagonist such as nimodipine and are targeted to develop a multitarget therapeutic strategy to confront AD. Tacripyrines are selective and potent ACNE inhibitors in the nanomolar range. The mixed type inhibition of hAChE activity of compound 11 (IC50 105 +/- 15 nM) is associated to a 30.7 +/- 8.6% inhibition of the proaggregating action of ACNE on the A beta and a moderate inhibition of A beta self-aggregation (34.9 +/- 5.4%). Molecular modeling indicates that binding of compound 11 to the ACNE PAS mainly involves the (R)-11 enantiomer, which also agrees with the noncompetitive inhibition mechanism exhibited by p-methoxytacripyrine 11. Tacripyrines are neuroprotective agents, show moderate Ca2+ channel blocking effect, and cross the blood-brain barrier, emerging as lead candidates for treating AD.. - MEC [AP20020576]; Fundacion Tedfilo Hernando [BF12003-02722, SAF2006-08764-C02-01, SAF-2006-08540, SAF2006-1249, CTQ2005-09365]; CAM [S/SAL-0275-2006]; ISCIII ; Red RENEVAS [RD06/0026/1002]; CSIC-GRICES [2007PT-13]. - J.M.C. thanks Dr. MSUPa/SUP. Luz de la Puente (Analytical Technologies Department, Lilly SA), and Dr. Ma. Angeles Martinez-Grau (Lilly SA) for the resolution of compound 11. J.M.C. and also R.L. thank MEC for a fellowship (AP20020576) and B.L. thanks CSIC for a I3P Training Contract. The present work has been supported by Fundacion Tedfilo Hernando, MEC grants BF12003-02722; SAF2006-08764-C02-01, SAF-2006-08540, SAF2006-1249, and CTQ2005-09365, CAM (S/SAL-0275-2006), ISCIII [Red RENEVAS (RD06/0026/1002)], CSIC-GRICES project (2007PT-13), and Fundacidn La Caixa (Barcelona, Spain).